ANALISIS PENGELOLAAN DANA OTONOMI KHUSUS PADA PEMERINTAH KABUPATEN SORONG - Frasawi, Jusuf Habel; Tinangon, Jantje; Warongan, Jessy D. L. (Universitas Sam Ratulangi, 2021)
This study aims to analyze how the Special Autonomy Fund is managed in the Sorong Regency Government, as well as to analyze the obstacles and efforts in managing the Special Autonomy Fund in the Sorong Regency Government. The research method used is a qualitative research method with a case study approach. Key informants who were interviewed with specific considerations and goals. Triangulation technique is used to test the validity of data and data sources. The transcript data described from the interview results were analyzed using analytical methods consisting of providing themes / coding, conceptualizing scientific statements and interpreting them in narrative form.The results showed that the Special Autonomy Fund (DOK) management mechanism was in accordance with the applicable provisions, namely the Governor Regulation of West Papua Province No. 53 of 2018 concerning the Management and Administration of the Special Autonomy Fund in West Papua Province. However, the management of the Special Autonomy Fund in Sorong Regency still found several obstacles, namely external, bureaucratic and communication constraints. Meanwhile, efforts to overcome these obstacles are communication and bureaucratic efforts.